Structure-performance relationships of commercial cathode gas diffusion layers in high-temperature PEM fuel cells - Won, Ahyeon; Agarwal, Harshal; Ranganath, Suresha; Torris, Arun; Cremers, Carsten; Tubke, Jens (Fuel Cells, 2026)
The influence of cathode gas diffusion layer (GDL) architecture on the performance of high-temperature proton exchange membrane fuel cells (HT-PEMFCs) remains insufficiently understood, particularly for commercially available materials with different substrate and microporous layer (MPL) designs. In this study, six commercial cathode GDLs were systematically compared using polarization analysis, electrochemical impedance spectroscopy, contact-angle measurement, scanning electron microscopy, mercury intrusion porosimetry, x-ray computed tomography, and COMSOL simulation. SGL 36BB and 22BB showed the best performance under both H2/Air and H2/O2, reaching maximum power densities of 0.445 +/- 0.005 and 0.426 +/- 0.011 W/cm2, whereas H23C2 performed worst at 0.302 +/- 0.008 W/cm2. The electrochemical and structural results indicate that backing-layer hydrophobic treatment and MPL architecture play a critical role in phosphoric acid management and transport losses, whereas porosity alone does not fully explain the observed performance ranking. The simulation reproduced the overall experimental trend for most GDLs, while the deviation observed for H23C2 suggests that acid-related effects should be more explicitly considered in future modeling of HT-PEMFC GDLs.
Keywords: COMSOL; equivalent circuit model (ECM); gas diffusion layer (GDL); high-temperature polymer electrolyte fuel cell (HT-PEMFC); Pore size distribution; porosity